Reconstructing the Arrival Direction of Cosmic Neutrinos with the Radio Neutrino Observatory Greenland (RNO-G) - Plaisier, Ilse (2022)
Neutrinos in the ultra-high energy regime are expected, either from astrophysical or cosmogenic origin. Due to the steeply falling neutrino flux for high energies, the currently largest neutrino detector has only observed neutrinos up to PeV energies. The Radio Neutrino Observatory in Greenland (RNO-G) will be sensitive in the PeV-EeV range. It uses the technique of detecting electromagnetic waves emitted by an in-ice neutrino induced particle shower. Radio waves can travel through the ice undisturbed for O(1km) and therefore large instrumented volumes can be built to be sensitive to the ultra-high energy regime. We developed a method for reconstructing the arrival direction of the neutrinos and the resulting angular resolution for RNO-G. Because the radio emission is observable on a cone of 56 degrees, the arriving radio signal is not aligned with the particle shower, which complicates the reconstruction of the incoming neutrino direction. For reconstructing the radio pulses, we will use a forward-folding technique, which forward folds an analytic electric-field model to match the obtained data as observed in the antennas. The radio technique is impacted by the irreducible thermal noise of the antennas, for which the forward folding technique has found to be very suitable. This thesis discusses the angular resolution, the event contours, which are very asymmetric, and the zenith dependent point spread function of the detector.